KORELASI KADAR HEMOGLOBIN DENGAN NILAI AMBANG DENGAR DI LINGKUNGAN BISING MESIN PADA PEKERJA PABRIK KONVEKSI - , Yayan Mitayani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Hearing loss due to noise exposure often caused by the noisy work environment. Many factors affect the rate and severity of hearing loss due to noise exposure, i.e: the intensity, the noise type, period of exposure per day, working duration and individual susceptibility. Noise exposure increase inner ear oxygen demand. Hemogobin levels is one of the factors that affect the oxygen transport to the tissues, including inner ears. The aim of this study was to know correlation between hemoglobin and hearing threshold of workers that exposed to noise. The study design was cross sectional with total sample are 63 samples. Each sample underwent pure tone audiometry for measuring hearing threshold and laboratory examination for determined haemoglobin consentration. There were 63 female samples, age range between 20-50 year old, working duration between 60-226 months. Spearman analysis showed there was correlation between hemoglobin level and bone conduction hearing threshold values at a frequency of 500 Hz in right ear (r=-0,365, p= 0,003) and 500 Hz left ear (r= - 0,282, p = 0,025). Correlation between hemoglobin concentration and air conduction hearing threshold values at a frequency of 500 Hz, 8000 Hz right ear are r = -0,229 , p = 0,017 and r= -0,257, p = 0,042 respetively, while at 500 Hz left ear was r = -0,258, p= 0,041. Conclusion: there was a negative correlation between hemoglobin levels and bone conduction and hearing threshold values at a frequency of 500 Hz right ear and 500 Hz left ear, air conduction at a frequency of 500 Hz, 8000 Hz right ear and 500 Hz left ear that was exposed to loud enough and long duration noise.